2014
DOI: 10.1186/2193-1801-3-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vaginal closure technique on early post-operative pain following vaginal prolapse surgery: a feasibility pilot study and qualitative assessment

Abstract: BackgroundSurgery for pelvic organ prolapse is a common surgical procedure. There is little research studying post-operative pain, contrasting with extensive literature on pain after childbirth trauma which shows that suture method has a significant effect on pain. We designed a protocol for a trial comparing suture techniques and post-operative pain, and conducted a pre-protocol pilot to inform our trial design.MethodsRoutine surgical data, post-operative pain scores (from 10 cm Visual Analogue Scales, VAS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
178
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(193 citation statements)
references
References 16 publications
9
178
6
Order By: Relevance
“…Most genetic diversity studies in plants have focused on ITS1 and ITS2 regions 3438 . However, our study demonstrates that there is sufficient genetic diversity in the ribosomal gene regions for evolutionary analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Most genetic diversity studies in plants have focused on ITS1 and ITS2 regions 3438 . However, our study demonstrates that there is sufficient genetic diversity in the ribosomal gene regions for evolutionary analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Koul et al [72] showed a correlation between transcript accumulation and Bt protein in different transgenic tomato lines expressing the cry1Ab transgene. Olsen et al [73] found that the developmental decline in bioefficacy (against Helicoverpa armigera ) in field-grown plants was associated with reduced cry1Ac transcript levels and Bt toxin levels in postsquaring cotton.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, besides in vitro studies, several interesting in vivo studies have been presented. 16,17 It is stated that plasma can selectively treat cancer cells, while leaving the healthy cells undamaged, 2,3,18,19,2325 and up to now, cancer cells have not yet developed resistance against plasma treatment. 2,3 Furthermore, there is a synergistic effect of plasma treatment and traditional therapies.…”
Section: Introductionmentioning
confidence: 99%